Applications of oxidized alginate in regenerative medicine. Issue 12 (8th March 2021) - Kong, Xiaoli; Chen, Long; Li, Bo; Quan, Changyun; Wu, Jun
Abstract : Because of its ideal degradation rate and features, oxidized alginate (OA) is selected as an appropriate substitute and has been introduced into hydrogels, microspheres, 3D-printed/composite scaffolds, membranes, and electrospinning and coating materials. Abstract : Because of its ideal degradation rate and features, oxidized alginate (OA) is selected as an appropriate substitute and has been introduced into hydrogels, microspheres, 3D-printed/composite scaffolds, membranes, and electrospinning and coating materials. By taking advantage of OA, the OA-based materials can be easily functionalized and deliver drugs or growth factors to promote tissue regeneration. In 1928, it was first found that alginate could be oxidized using periodate, yielding OA. Since then, considerable progress has been made in the research on the modification and application of alginate after oxidation. In this article, we summarize the key properties and existing applications of OA and various OA-based materials and discuss their prospects in regenerative medicine.